Social and psychological effects of circumcision: A narrative review - Bahattin Aydoğdu; Mustafa Azizoğlu; Mehmet Hanifi Okur (Chakra Brahmanda Lentera Institute, 2022)
Descriptions of penile circumcision have focused primarily on disease, dysfunction, or sensation, with relatively little consideration of the psychological and psychosocial implications of the procedure. It is also reported to be of interest regarding potential qualitative changes in the subjective experience of sexual activity following changes in penile anatomy (removal of the foreskin) or related sexual biomechanics. Circumcision indeed has psychological, psychosocial, and psychosexual effects. The differences in circumcisions performed during infancy, childhood, and adulthood are remarkable. There are also potential psychosocial effects on parents who may or may not choose circumcision for their children. We argue that additional attention should be paid to the potential for long-term effects of the procedure, which may not be appropriately considered when the patient is an infant or child.